CONCEPT OF CLEANER PRODUCTION APPROACH AND ZERO LIQUID DISCHARGE SYSTEM IN THE TANNERY INDUSTY - Atiqa Rahmawati (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Tanning industry is one of the industries that produces tannery waste water (TWW) which is dangerous to the environment. About 250 kg leather generating 15,000-50,000 of waste water. This increase environmental concerns regarding TWW. In this review, discussed the concept cleaner production (CP) approach at each process stage in the tannery process and the Zero liquid discharge (ZLD) system used in processing tannery liquid waste. The application of CP in the leather tanning industry is by substituting chemicals with environmentally friendly materials, management water, optimizing tanning conditions, and using technology to recycle and reuse liquid waste. The application of the ZLD system is one of the CP approach for recycle and reuse TWW. The ZLD system used in leather tanning is the Thermal-based ZLD system and Reverse Osmosis. Several countries have implemented the ZLD system, are the United States, India, China, European Union countries and Middle East. The ZLD system is an important TWW strategy to be implemented globally, although operating costs and high energy consumption are limitations in its application. Technological advances and exploration of new approaches to overcome the limitations of ZLD technology may make the approach more feasible and sustainable in the future.